Evaluating and redesigning the teaching practices of the Kazakh Mythology- engraving techniques. - Karim Baigutov; Aman Ibragimov; Alzhanov Gadilbek Kh; Kumarkan Muratayev; Taiyrzhan Iskakov; Dzhanaev Miyat (PLoS ONE, 2024)
The study was designed to explore and develop art students' interest and engagement in Kazakh mythology and using engraving techniques. The archetypic and challenges of Kazakh mythology in art students were not previously explored. Therefore, the need for study in this domain was essential to cover the gap in the literature. The gap has been recently discovered by Kazakh scholars although it has been explored by foreign authors but the authenticity of such studies remains a question. The study was experimental and the results show a strong association between art's student's engagement with Kazakh mythology using engraving techniques. Moreover, the elective course was selected by 90% class of the art students voluntarily. The teaching method developed for the study provides strong results and the outcome of the experiment was well above 80%. The study used a systematic method along with comparative analysis based on Kazakh myths, culture, ethnology, folklore, mythology, and archeology.